Coinhibitory Molecule PD-1 as a Therapeutic Target in the Microenvironment of Multiple Myeloma - Atanackovic, Djordje; Luetkens, Tim; Radhakrishnan, Sabari; Kroger, Nicolaus (Current Cancer Drug Targets, 2017)
Background: Patients with Multiple Myeloma suffer from dysregulation of the immune system and new therapeutic options targeting the immune systems such as monoclonal antibodies or specific Cell therapy such as CAR-T cells have entered clinical practice, but the exhausted immune system hampered a more effective immunotherapy. Targeting the immunological dysfunction in the microenviroment might be a potential target for immune-mediated therapies. Method: Here we review the current literature and knowledge about the programmed death 1 (PD-1) receptor which is expressed on the surface of exhausted T and B cells and its ligand PD-L1 is expressed on myeloma cells and inhibits T cell-mediated apoptosis. Results: The programmed death 1 (PD-1) receptor is expressed on the surface of exhausted T and B cells and its ligand PD-L1 is expressed on myeloma cells and inhibits Tcell-mediated apoptosis. Inhibiting such “checkpoint” by monoclonal antibodies recently has been shown high activity in solid tumors and malignant lymphomas. In patients with multiple myelomaPD-L1 is overexpressed on myeloma cells and PD1 on T-cells suggesting an active role of PD-1/PD-L1 in the immunosuppressive microenvironment. Conclusion: Immunotherapies using anti-PD-1/PD-L1 strategies are a promising treatment options for patients with multiple myeloma.
Keywords: microenvironment